Religion in the Roman Empire - Rüpke, Jörg; Versluys, Miguel John; Antes, Peter; Hutter, Manfred; Gordon, Richard; Petridou, Georgia; Rieger, Anna-Katharina; Wendt, Heidi; Raja, Rubina; Andringa, William van; Woolf, Greg (Die Religionen der Menschheit, 2021)
"The Roman Empire was home to a fascinating variety of different cults and religions. Its enormous extent, the absence of a precisely definable state religion and constant exchanges with the religions and cults of conquered peoples and of neighbouring cultures resulted in a multifaceted diversity of religious convictions and practices. This volume provides a compelling view of central aspects of cult and religion in the Roman Empire, among them the distinction between public and private cult, the complex interrelations between different religious traditions, their mutually entangled developments and expansions, and the diversity of regional differences, rituals, religious texts and artefacts"--Back cover